High-salinity wastewater treatment membrane and preparation method thereof
Through the use of high -density polyethylene and modified palm silk materials, high -salt wastewater treatment membranes are used to solve the problem of pollution resistance and fragile in the existing technology, and the mechanical performance improvement of the membrane and the optimization of wastewater treatment performance.
Patent Information
- Application Number
- CN202411967466.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wastewater treatment, and in particular to a high-salt wastewater treatment membrane and a preparation method thereof. Background Art
[0002] High-salt wastewater refers to wastewater with a total salt content of at least 1%, mainly from concentrated wastewater generated during the production process, concentrated water generated during the desalination process, concentrated wastewater from reverse osmosis or continuous electrodialysis (EDI) or electrodialysis in desalination stations, etc. This type of wastewater usually has inorganic salts, high salt content, complex composition, large differences in chemical properties, severe scaling tendency, and great difficulty in treatment. As environmental protection regulations become increasingly stringent, these wastewaters cannot be discharged directly.
[0003] Zero discharge of industrial wastewater is one of the important ways to solve my country's water resource problems. It is increasingly used in the fields of power plant wastewater, coal chemical wastewater, etc., mainly reflected in water treatment technology based on membrane method. The water treated by membrane method is recycled to improve the efficiency of water use. It can not only effectively intercept pollutants in wastewater and reduce environmental pollution, but also recycle and reuse valuable components in industrial wastewater, save more resources, and effectively realize environmental protection and energy saving, so as to achieve water resource reuse and obtain better economic results.
[0004] However, in water treatment technologies that mainly use membrane methods, the membrane is not resistant to pollution, is easy to dehydrate, and is fragile during use. It also has poor mechanical properties, which shortens the service life of the membrane.
[0005] Therefore, there is an urgent need to develop a durable membrane for high-salinity wastewater treatment. Summary of the invention
[0006] In order to solve the above technical problems, the present application provides a high-salt wastewater treatment membrane and a preparation method thereof.
[0007] The present application provides a high-salt wastewater treatment membrane, which specifically includes the following components in parts by weight: High-density polyethylene 25-30 parts, modified palm fiber 4-8 parts, Span 60 2-4 parts, catalyst 0.5-1.5 parts, regulator 0.3-0.8 parts; The preparation method of the modified palm fiber is as follows: placing palm fiber and nanometer-scale inorganic particles in a 15-25wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuging, drying and grinding to obtain the modified palm fiber; the weight ratio of the palm fiber, the nanometer-scale inorganic particles and the 15-25wt% cysteamine hydrochloride solution is 14-20:1-5:100; The regulator is selected from one or more of thioglycolic acid, mercaptopropionic acid, mercaptoethanol, and p-toluenesulfonic acid.
[0008] The present application adopts the above-mentioned technical scheme to prepare modified palm fiber, and selects one or more of thioglycolic acid, mercaptopropionic acid, mercaptoethanol, and p-toluenesulfonic acid as regulators, and combines them with high-density polyethylene, Span 60, a catalyst, and a regulator. At the same time, the amount of each raw material component is controlled. The obtained high-salt wastewater treatment membrane has good mechanical properties and aging resistance. At the same time, the water flux and wastewater treatment performance of the high-salt wastewater treatment membrane prepared by the technical scheme of the present application are better.
[0009] The present application utilizes the natural S-shaped and Z-shaped grooves on palm fibers to enable nano-scale inorganic particles to be fully adsorbed on the fibers of palm fibers, thereby enhancing the toughness of the high-salt wastewater treatment membrane and providing better mechanical properties; cysteamine hydrochloride as a solvent can reduce the hardness of palm fibers and improve the applicability of palm fibers.
[0010] The high-salinity wastewater treatment membrane uses high-density polyethylene and modified palm fiber as the main raw materials and can form a three-dimensional network structure with other substances, which further enhances the mechanical properties of the treatment membrane; at the same time, the high-salinity wastewater treatment membrane with a skeleton structure has the characteristics of strong flocculation, fast precipitation, and strong capture force, with high flux and retention rate, and can treat Ni in wastewater. 2+ Cr 6+ And other heavy metals.
[0011] Preferably, in the method for preparing the modified palm fiber, the weight ratio of the palm fiber, the nanoscale inorganic particles and the 15-25wt% cysteamine hydrochloride solution is 15-19:2-4:100.
[0012] Through experimental analysis, it can be known that the present application selects the above-mentioned weight ratio of palm fiber, nano-scale inorganic particles and cysteamine hydrochloride solution to prepare modified palm fiber, which can further improve the performance of the treatment membrane.
[0013] Preferably, the modification reaction conditions are: temperature of 70-90° C., and reaction time of 90-150 min.
[0014] Preferably, the nanometer-scale inorganic particles are selected from one or more of nanometer calcium silicate particles, nanometer calcium carbonate particles, sericite particles, and nanometer silicon dioxide particles; and the average particle size of the nanometer-scale inorganic particles is 30-80 nm.
[0015] Preferably, the regulator is composed of a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:1-3.
[0016] Through experimental analysis, it can be known that the present application selects mercaptoethanol and p-toluenesulfonic acid in the above weight ratio as regulators, which can further improve the performance of the treatment membrane.
[0017] Preferably, the catalyst is selected from one or more of sodium hypophosphite, triethylenediamine, 4-dimethylaminopyridine, dibutyltin dilaurate, and N-hydroxysuccinimide.
[0018] In a second aspect, the present application provides a method for preparing the above-mentioned high-salt wastewater treatment membrane, which specifically comprises the following steps: The high-density polyethylene, the catalyst, and the regulator are uniformly mixed and first kneaded to obtain a resin mixed liquid; Adding the modified palm fiber, acetone and Span 60 into the resin mixture, and performing a second mixing to obtain a casting solution; The casting solution is matured, then a film is scraped on a glass plate, and then solidified into a film in anhydrous ethanol at 0° C., thereby obtaining the high-salt wastewater treatment membrane.
[0019] Preferably, the first mixing and kneading parameters are: temperature of 130-160° C., and time of 20-30 min.
[0020] Preferably, the second mixing parameters are as follows: temperature is 160-190° C., and time is 30-50 min.
[0021] Preferably, the aging parameters are: temperature of 60-80° C. and time of 5-7 h.
[0022] In summary, the technical solution of this application has the following effects: The present application adopts the method of placing palm fibers and nanometer-sized inorganic particles in a cysteamine hydrochloride aqueous solution for modification reaction to prepare modified palm fibers, and selecting one or more of thioglycolic acid, mercaptopropionic acid, mercaptoethanol, and p-toluenesulfonic acid as regulators, combining them with high-density polyethylene, Span 60, a catalyst, and a regulator, while controlling the amount of each raw material component. The obtained high-salt wastewater treatment membrane has good mechanical properties and aging resistance. At the same time, the high-salt wastewater treatment membrane prepared by the technical solution of the present application has better water flux and wastewater treatment performance.
[0023] This application further improves the performance of the high-salinity wastewater treatment membrane by further optimizing the preparation method of modified palm fiber and screening the types of regulators. DETAILED DESCRIPTION
[0024] The palm fibers in this application were purchased from Tianjin Jiajia Green Product Technology Co., Ltd., and high-density polyethylene (5000S) was purchased from Yangzi Petrochemical; the remaining raw materials or reagents can be obtained through ordinary commercial purchases.
[0025] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application. Example Examples 1-3
[0026] Examples 1-3 each provide a high-salt wastewater treatment membrane.
[0027] The difference between the high-salt wastewater treatment membranes in the above embodiments is that the amounts of the raw materials of each component in the high-salt wastewater treatment membranes are different, as shown in Table 1.
[0028] The specific steps of the preparation method of the high-salt wastewater treatment membrane in the above embodiment are as follows: The preparation method of modified palm fiber is as follows: 17g of palm fiber and 3g of nano-scale calcium silicate particles (average particle size of 50nm) are placed in 100g of 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 200 meshes to obtain modified palm fiber; the modification reaction temperature is 80℃, and the reaction time is 120min; High-density polyethylene, catalyst dibutyltin dilaurate, and a regulator (composed of a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:2) were uniformly mixed, and kneaded at a temperature of 145°C for 25 minutes to obtain a resin mixture; Add modified palm fiber, 20g acetone and Span 60 into the resin mixture, mix at 175°C for 40min, and continue mixing to obtain a casting solution; The casting solution was matured at 70°C for 6 hours, then scraped on a glass plate to a thickness of 100 μm, and solidified into a film in anhydrous ethanol at 0°C to obtain a high-salt wastewater treatment membrane.
[0029] Table 1 The amount of raw materials of each component in the high-salinity wastewater treatment membrane Embodiment 4-10
[0030] Examples 4-10 each provide a high-salt wastewater treatment membrane.
[0031] The difference between the above embodiment and embodiment 2 is that the preparation method of the modified palm fiber is different, as shown below.
[0032] In Example 4: The preparation method of modified palm fiber is as follows: 15g of palm fiber and 4g of nano calcium silicate particles (average particle size of 50nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the modification reaction temperature is 70℃, and the reaction time is 150min.
[0033] In Example 5: The preparation method of modified palm fiber is as follows: 19g of palm fiber and 2g of nano calcium silicate particles (average particle size of 50nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the temperature of the modification reaction is 90℃, and the reaction time is 70min.
[0034] In Example 6: The preparation method of modified palm fiber is as follows: 20g of palm fiber and 1g of nano calcium silicate particles (average particle size of 50nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the temperature of the modification reaction is 80℃, and the reaction time is 120min.
[0035] In Example 7: The preparation method of modified palm fiber is as follows: 14g of palm fiber and 5g of nano calcium silicate particles (average particle size of 50nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the temperature of the modification reaction is 80℃, and the reaction time is 120min.
[0036] In Example 8: The preparation method of modified palm fiber is as follows: 17g of palm fiber and 3g of nano calcium silicate particles (average particle size of 10nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the temperature of the modification reaction is 80℃, and the reaction time is 120min.
[0037] In Example 9: The preparation method of modified palm fiber is as follows: 17g of palm fiber and 3g of nano calcium silicate particles (average particle size of 100nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the temperature of the modification reaction is 80℃, and the reaction time is 120min.
[0038] In Example 10: The preparation method of modified palm fiber is as follows: 17g of palm fiber and 3g of nano calcium silicate particles (average particle size of 50nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the modification reaction temperature is 100℃, and the reaction time is 80min.
[0039] The remaining raw material components of the high-salinity wastewater treatment membrane, the amounts of each raw material component, and the preparation method of the high-salinity wastewater treatment membrane in the above embodiment and embodiment 2 are the same. Examples 11-14
[0040] Examples 11-14 each provide a high-salt wastewater treatment membrane.
[0041] The difference between the above embodiment and embodiment 2 is that the types of regulators are different, as shown below.
[0042] In Example 11: the regulator is composed of a mixture of thioglycolic acid and p-toluenesulfonic acid in a weight ratio of 9:2.
[0043] In Example 12: the regulator is composed of a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:0.5.
[0044] In Example 13: the regulator is composed of a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:1.
[0045] In Example 14: the regulator is composed of a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:3.
[0046] The remaining raw material components of the high-salinity wastewater treatment membrane, the amounts of each raw material component, and the preparation method of the high-salinity wastewater treatment membrane in the above embodiment and embodiment 2 are the same. Comparative Example Comparative Example 1
[0047] This comparative example provides a high-salt wastewater treatment membrane.
[0048] The difference between the high-salt wastewater treatment membrane in this comparative example and that in Example 2 is that the dosage of each component raw material in the high-salt wastewater treatment membrane is different, as shown in Table 1.
[0049] The remaining raw material components, the amounts of the raw material components, and the preparation method of the high-salt wastewater treatment membrane in this comparative example and Example 2 are the same. Comparative Examples 2-3
[0050] Comparative Examples 2-3 each provide a high-salt wastewater treatment membrane.
[0051] The difference between the comparative example and Example 2 is that the preparation method of the modified palm fiber is different, as shown below.
[0052] In Comparative Example 2: The preparation method of modified palm fiber is as follows: 22g of palm fiber and 0.5g of nano-scale calcium silicate particles (average particle size of 50nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80°C, and ground to 10-30 mesh to obtain modified palm fiber; the temperature of the modification reaction is 80°C, and the reaction time is 120min.
[0053] In Comparative Example 3: The preparation method of the modified palm fiber is as follows: 17g of palm fiber and 3g of montmorillonite (average particle size of 50nm) are placed in 100g, 20wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuged at 6000rpm for 10min, dried at 80℃, and ground to 10-30 mesh to obtain modified palm fiber; the temperature of the modification reaction is 80℃, and the reaction time is 120min.
[0054] The remaining raw material components, the amounts of the raw material components, and the preparation method of the high-salt wastewater treatment membrane in the above comparative example and Example 2 are the same. Comparative Example 4
[0055] This comparative example provides a high-salt wastewater treatment membrane.
[0056] The amounts of the raw material components of the high-salt wastewater treatment membrane in this comparative example and Example 2 are the same.
[0057] The specific steps of the preparation method of the high-salt wastewater treatment membrane in this comparative example are as follows: High-density polyethylene, catalyst dibutyltin dilaurate, and a regulator (composed of a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:2) were uniformly mixed, and kneaded at a temperature of 145°C for 25 minutes to obtain a resin mixture; Add palm fiber, nano-scale calcium silicate particles (average particle size of 50 nm), acetone 20 g, and Span 60 into the resin mixture, mix at 175°C for 40 min, and continue mixing to obtain a casting solution; The casting liquid was matured at 70°C for 6 hours, then scraped on a glass plate to a thickness of , and solidified into a film in anhydrous ethanol at 0°C to obtain a high-salt wastewater treatment membrane. Comparative Examples 5-6
[0058] Comparative Examples 5-6 each provide a high-salt wastewater treatment membrane.
[0059] The difference between the comparative example and Example 2 is that the types of regulators are different, as shown below.
[0060] In Comparative Example 5: the regulator is vinyl distearamide.
[0061] In Comparative Example 6, the regulator is composed of a mixture of mercaptoethanol and 3,3'-diallylbisphenol A in a weight ratio of 9:2.
[0062] The remaining raw material components, the amounts of the raw material components, and the preparation method of the high-salt wastewater treatment membrane in the above comparative example and Example 2 are the same. Performance testing
[0063] Mechanical properties: The elastic tensile force and elongation at break of the high-salt wastewater treatment membrane were tested using an AGS-J universal material testing machine. The test temperature was room temperature and the tensile speed was 2 mm / min.
[0064] Thermal aging performance: According to the standard GB / T528-2009 test, the high-salt wastewater treatment membrane was placed at a constant temperature of 135°C for 336 hours, and then taken out to measure the tensile strength and elongation at break; Water flux performance: A cup-type ultrafilter was used to measure the water flux of the high-salt wastewater treatment membrane; the high-salt wastewater treatment membrane was pre-pressed at a pressure of 0.1 MPa for 15 min before the test; the water flux was calculated according to the formula J = V / (S*t); where J is the water flux of the membrane at a pressure of 0.1 MPa; V is the volume of the permeate in time t; S is the effective measurement area of the membrane; and t is the measurement time.
[0065] Wastewater treatment performance: The raw water sample comes from the desulfurization wastewater of the power plant: the ion concentration is Cr 6+ 89.72mg / L, Ni 2+ It is 103.80mg / L.
[0066] Test results: as shown in Table 2.
[0067] Table 2 Performance test results of high-salt wastewater treatment membranes in Examples 1-14 and Comparative Examples 1-6
[0068] Combined with Table 2, by comparing the test results of Examples 1-14 with those of Comparative Examples 1-6, the present application places palm fibers and nanoscale inorganic particles in a cysteamine hydrochloride aqueous solution for modification reaction to prepare modified palm fibers, and selects one or more of thioglycolic acid, mercaptopropionic acid, mercaptoethanol, and p-toluenesulfonic acid as a regulator, and combines them with high-density polyethylene, Span 60, a catalyst, and a regulator, while controlling the amount of each raw material component. The obtained high-salt wastewater treatment membrane has good mechanical properties and aging resistance. At the same time, the water flux and wastewater treatment performance of the high-salt wastewater treatment membrane prepared by the technical solution of the present application are better.
[0069] By comparing the test results of Examples 2, 4-10 with Comparative Examples 2-3, in the process of preparing modified palm fibers, the present application controls the weight ratio of palm fibers, nanoscale inorganic particles and cysteamine hydrochloride aqueous solution to be 14-20:1-5:100, which effectively improves the performance of the high-salt wastewater treatment membrane.
[0070] By comparing the test results of Examples 2, 11-14 with Comparative Examples 5-6, the present application selects one or more of mercaptoacetic acid, mercaptopropionic acid, mercaptoethanol, and p-toluenesulfonic acid as a regulator, which effectively improves the performance of the high-salinity wastewater treatment membrane. Furthermore, the present application uses a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:1-3 to form a regulator, which can further improve the performance of the high-salinity wastewater treatment membrane.
[0071] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A high-salinity wastewater treatment membrane, characterized in that: Specifically include the following components by weight: High-density polyethylene 25-30 parts, modified palm fiber 4-8 parts, Span 60 2-4 parts, catalyst 0.5-1.5 parts, regulator 0.3-0.8 parts; The preparation method of the modified palm fiber is as follows: placing palm fiber and nano-scale inorganic particles in a 15-25wt% cysteamine hydrochloride aqueous solution for modification reaction, and then centrifuging, drying and grinding to obtain the modified palm fiber; The weight ratio of the palm fibers, the nano-scale inorganic particles and the 15-25wt% cysteamine hydrochloride solution is 14-20:1-5:100; The regulator is selected from one or more of thioglycolic acid, mercaptopropionic acid, mercaptoethanol, and p-toluenesulfonic acid.
2. The high-salt wastewater treatment membrane according to claim 1, characterized in that: In the preparation method of the modified palm fiber, the weight ratio of the palm fiber, the nano-scale inorganic particles and the 15-25wt% cysteamine hydrochloride solution is 15-19:2-4:
100.
3. The high-salt wastewater treatment membrane according to claim 1, characterized in that: The conditions of the modification reaction are: temperature of 70-90°C and reaction time of 90-150min.
4. The high-salinity wastewater treatment membrane according to claim 1, characterized in that: The nanometer-scale inorganic particles are selected from one or more of nanometer calcium silicate particles, nanometer calcium carbonate particles, sericite particles, and nanometer silicon dioxide particles; and the average particle size of the nanometer-scale inorganic particles is 30-80 nm.
5. The high-salinity wastewater treatment membrane according to claim 1, characterized in that: The regulator is composed of a mixture of mercaptoethanol and p-toluenesulfonic acid in a weight ratio of 9:1-3.
6. The high-salinity wastewater treatment membrane according to claim 1, characterized in that: The catalyst is selected from one or more of sodium hypophosphite, triethylenediamine, 4-dimethylaminopyridine, dibutyltin dilaurate, and N-hydroxysuccinimide.
7. The method for preparing a high-salt wastewater treatment membrane according to any one of claims 1 to 6, characterized in that: The specific steps include: The high-density polyethylene, the catalyst, and the regulator are uniformly mixed and first kneaded to obtain a resin mixed solution; Adding the modified palm fiber, acetone and Span 60 into the resin mixture, and performing a second mixing to obtain a casting solution; The casting solution is matured, then a film is scraped on a glass plate, and then solidified into a film in anhydrous ethanol at 0° C., thereby obtaining the high-salt wastewater treatment membrane.
8. The method for preparing a high-salt wastewater treatment membrane according to claim 7, characterized in that: The parameters of the first mixing are as follows: temperature is 130-160° C., and time is 20-30 min.
9. The method for preparing a high-salt wastewater treatment membrane according to claim 7, characterized in that: The parameter conditions of the second mixing are: temperature of 160-190° C. and time of 30-50 min.
10. The method for preparing a high-salt wastewater treatment membrane according to claim 7, characterized in that: The aging parameters are as follows: temperature of 60-80° C. and time of 5-7 h.
Citation Information
Patent Citations
Active carbon fibre with nano-scale photocatalyst and processing method thereof
CN101209411A
Preparation method of cellulose nano-fiber / polyvinyl alcohol composite membrane
CN103387685A
Preparation method and application of modified cysteine palm bark adsorbent
CN103464119A
Nonwoven cloth composite nanofiltration membrane and preparation method and application thereof
CN105498550A
Method for preparing hydrophilic nanohybrid enhancement type hollow fiber membrane
CN106310967A